Design and analysis of solar energy for rural electrification in eco-tourism destination of Liogu Ku Silou-silou, Eplissi, Sabah - Maryon Eliza Matius (2023)
In search of a clean energy resource for a better environment and a 100% electrification rate, Malaysia has set a target to achieve 31% renewable energy contribution by 2025. However, in rural areas of Malaysia, especially Sabah and Sarawak, more than 50% of the population is below the poverty line as of 2017. To overcome these problems, this research intends to help in promoting renewable energy technology as a sustainable electricity generation mechanism, especially in rural areas where the national grid is not cost-effective due to challenging terrain in certain regions. The Eco-Tourism Destination of Liogu Ku Silou-Silou (EPLISSI), Kota Belud, Sabah, has been selected as the study site. This study aims to develop a small-scale off-grid solar PV system, analyze its performance, and find the most optimized design through simulation studies. Meanwhile, the method used to achieve the aims of this research includes the preliminary assessment, design development through the review of the past studies as well as computation and components’ selection, components’ fabrication and testing, and installation of the system and measuring devices. As for the simulation studies, the ESCoBox tool, Global Solar Atlas version 2.3 (GSA 2.3), and HOMER software were used. The ESCoBox and GSA 2.3 softwares were used in the preliminary study (i.e., before the photovoltaic (PV) system installation) to generate the load profiles, and to select the approximate size of the PV panel system, respectively. While the HOMER software optimises the system (post PV system installation) on the existing system. As a result, it is found that the EPLISSI’s condition based on solar radiation and location are suitable for solar PV system installation. Before system installation, the GSA 2.3 web tool suggested that an energy output of 8.72 kWh/day can be generated from a 2.5 kWp solar PV system. This system can at least satisfy the ESCoBox’s result of daily total average energy demand by EPLISSI of 4.6 kWh/day. As for the actual installation, the installed solar power capacity was 2.48 kWp (i.e., eight 310 W solar panels were used), together with 12 lead-acid batteries (i.e., 12 V, 100 Ah battery capacity). A 12-month worth of fieldwork data consisting of actual load demand, solar radiation, and wind speed were collected and used as inputs for the HOMER software. It was found that the existing installed system (i.e., termed as the first condition in the HOMER data analysis stage) in EPLISSI was not optimally designed, as a 14.3% capacity shortage exists. This PV system configuration also has a higher net present cost (NPC) and cost of electricity (COE) under the 15% maximum annual capacity shortage (MACS) limit. Using the actual electrical load demand and the on-site solar radiation data, the HOMER software suggested that an optimized system (second condition with 15% MACS) should consist of 5 kWp solar PV with 8 lead-acid batteries. This optimized system would be better in terms of the NPC (from RM 95836.15 to RM 91791.88, hence a reduction of 5.30%) and capacity shortage (from 14.3% to 13.5%, thus a reduction of 0.80%) compared to the existing system (first condition) in EPLISSI. Lastly, there exist 40% difference between the recommended PV capacity GSA 2.3, 2.5 kWp and HOMER, 1.5 kWp (in case of C2-SB). Smaller PV capacity is optimal for C2-SB system due to the incorporation of diesel generator (DG). This also result in lower NPC (from RM 95836.15 to RM 73918.00, hence a reduction of 22.87%) of the system.